Somatochlora shennong sp. nov. from Hubei, China (Odonata: Corduliidae) - Zhang, Hao-Miao; Vogt, Timothy E.; Cai, Qing-Hua (Zootaxa, 2014)
A new species, Somatochlora shennong sp. nov. (holotype ♂, Dajiuhu National Wetland Park in Shennongjia National Nature Reserve, Hubei Province, China, 9 August 2012) is described, illustrated, and compared with the related species S. dido Needham and S. taiwana Inoue & Yokota.